Facile Surface Modification Of Graphene Nanoplatelets (GNPS) Using Covalent ATPS-Dehydration (GNPS-ATPS) And Non-Covalent Polyetherimide Adsorption (GNPS-PEI) Method - Abd Razak, Jeefferie; Ahmad, Sahrim; Ratnam, Chantara Thevy; Yaakub, Juliana; Mohd Abid, Mohd Asyadi Azam; Zainal Abidin, Muhammad Zaimi; Abd Manaf, Mohd Edeerozey; Mohamad, Noraiham (Trans Tech Publications Inc., 2014)
-